A survey of TQM practices in the Malaysian electrical and electronic industry - Quek, Eng Eng; Mohd. Yusof, Sha'ri (Taylor and Francis Group, 2003)
Total quality management (TQM) is one of the key approaches towards realizing the goal of meeting customer satistaction. Besides eﬀorts for quality improvement by large companies, many small and medium-sized enterprises (SMEs) have also pursued their quality improvement eﬀort, but mostly through the ISO 9000 certiﬁcation route. Few of these SMEs have actually implemented a total approach using the TQM philosophy. This paper relates to a survey conducted to investigate the level of practice on TQM elements and to ﬁnd the most critical factors perceived by the SMEs. A questionnaire was sent to 248 companies in the electrical and electronics sector in Malaysia, which resulted in a response rate of 24.2%. Attempts at ﬁnding signiﬁcant diﬀerences between small and large companies’ quality practices were made and revealed that there was a signiﬁcant diﬀerence between the TQM practices of large and small companies. Management leadership, continuous improvement system and education and training proved to be rated among top priorities for successful implementation by large companies, compared with SMEs. However, supplier quality management was found to be the least implemented criteria by both large and small companies. This indicates that a much greater emphasis must be given on supplier management in future quality improvement programmes. The study has highlighted the importance of TQM adoption in SMEs to meet future challenges in realizing the vision, of world-class organizations. Engineering innovation must not be limited to ‘hard technology’ alone but should incorporate advanced manufacturing management techniques to sustain the improvement eﬀorts and in meeting the long-term needs of the nation. Further studies can be made focusing on other types of industry in Malaysia, such as automotive, metal-based, and food processing, etc, to allow for a more comprehensive TQM framework to be built upon to meet the needs of SMEs in their drive towards a total quality organization